(untitled) (REMUNOM, 2023)
ABSTRAT The purpose of this article, whose theme addresses CRIMINALITY AND INFORMATION AND COMMUNICATION TECHNOLOGIES, is to emphasize the cases that have already happened and are happening, as well as the laws that protect the problem, aiming at the possibilities or impossibilities that remain to control or avoid crimes that are practiced through the Internet, highlighting which protection rules should be taken to avoid crimes, in the same way that actions can be used in the event of suffering a crime in this way. This research also aims to explore the advance of criminal law in the face of new technologies. With the aim of clarifying the technological revolution and its positive and negative effects on society’s daily life; addressing various virtual crimes that are little mentioned by legal scholars. However, Brazil currently lacks considerable legislation to preserve security in the virtual space. There are difficulties in carrying out investigations in many cases. However, it can be concluded that criminal law and, consequently, legislation tends to progress in order to keep up with social dynamics, otherwise it will become inapplicable to specific cases. Key words: Technologies; Virtual Crimes; Internet;